PENGARUH STRES DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Bank Syariah Mandiri KCP. Pekanbaru Panam) - Sri Rahmi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of stress and work conflict on employee performance at the independent Islamic bank PT. Pekanbaru Panam. Where two independent variables and one dependent variable are proposed, namely work stress and work conflict as independent variables and employee performance as dependent variables. This research method is descriptive and quantitative by using the SPSS 21 program, where the sample used is the employee of Mandiri Syariah Bank PT. Pekanbaru Panam with 33 respondents. For sampling technique using census method. Techniques of data collection through questionnaires and interview. The result of the analysis using validity test, reliability test, determination test, simple regretion test, multiple linear regression test, t test, and f test, so that it can be seen that work stress has negative and significant effect on employee performance, that work conflict has negative and significant effect on employee performance, and that stress and work conflict have a significant effect on employee performanceKeywords : work stress, work conflict, and employee performance